2018
DOI: 10.3390/f9020090
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Firewood Movement by the Public: Use of Survey Data to Assess and Improve Efficacy of a Regulatory and Educational Program, 2006–2015

Abstract: This paper describes a program of policy management and research from 2006 through 2015. It focuses on regulator efforts to understand and address challenges presented by dispersal of forest diseases and invasive pests in firewood by the camping public. Five surveys conducted at two-year intervals informed these efforts. The first survey in 2006 benchmarked campers' awareness of forest threats by invasive species, their evaluations of firewood supplied at and near Wisconsin state parks, and their compliance wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Results from the surveys suggest there were positive changes in people's behaviors and that mild regulation coupled with persuasive education was successful in reducing the movement of firewood [66,67]. The studies also found that perceived peer pressure and disapproval from close social groups such as friends and family could influence whether people actively moved firewood [68].…”
Section: Engage In Early Outreach Involving Stakeholders In Decisionmentioning
confidence: 93%
“…Results from the surveys suggest there were positive changes in people's behaviors and that mild regulation coupled with persuasive education was successful in reducing the movement of firewood [66,67]. The studies also found that perceived peer pressure and disapproval from close social groups such as friends and family could influence whether people actively moved firewood [68].…”
Section: Engage In Early Outreach Involving Stakeholders In Decisionmentioning
confidence: 93%
“…Many of the same biosecurity measures used in terrestrial and freshwater management can be implemented in marine ecosystems through policy, legislation, and informational campaigns (e.g., enforced border management of overseas goods in New Zealand, Champion 2018; firewood restrictions for fungal pathogens, Diss-Torrance et al 2018). The aquarium trade and ballast water discharge are two major sources of anthropogenic pathogen movement in coastal systems.…”
Section: General Outbreak Prevention Strategiesmentioning
confidence: 99%
“…There is very little evidence about how best to engage with recreationists about tree health and plant biosecurity in order to increase awareness and change behaviours. This section draws on seven studies that have reported evaluations of biosecurity engagement and education campaigns in the U.S.A., Australia, New Zealand and the U.K. Two studies focussed on programmes aimed at preventing the movement of firewood by U.S.A. campers to stop the spread of tree borers [ 32 , 33 ]. Another study with recreationists in Australia explored an education programme concerning the spread of a root rotting fungus [ 34 ].…”
Section: Effectiveness Of Behavioural Change Interventions Relating Tmentioning
confidence: 99%
“…Two examples of campaigns that achieved some success in terms of behavioural change of recreationists both combine the provision of information with practical resources and biosecurity equipment. Campaigns aimed at U.S.A. campers regarding the movement of firewood seem to have had some success at reducing the numbers of campers transporting firewood from places outside of campsites through understanding their motivations and behaviours [ 32 , 33 ]. This program also made it easier for campers to purchase firewood on-site on their arrival, thus reducing the cost (in terms of effort) to recreationists.…”
Section: Effectiveness Of Behavioural Change Interventions Relating Tmentioning
confidence: 99%